Effects of water table level on soil CO2 respiration in West Kalimantan forested and bare peatland: An experimental stage - DWI ASTIANI; BURHANUDDIN BURHANUDDIN; MUHAMMAD TAHERDJADEH; LISA M. CURRAN (Nusantara Bioscience, 2016)
Abstract. Astiani D, Burhanuddin, Taherdjadeh M, Curran LM. 2016. Effects of water table level on soil CO2 respiration in West Kalimantan forested and bare peatland: An experimental stage. Nusantara Bioscience 8: 201-206. Peatland forest is one of ecosystems that are susceptible to the alterations of water regimes. Our previous study demonstrated that hydrologic conditions are predominant variables in determining carbon respiration rates from peat soils. However, we have limited empirical measures of how hydrologic conditions (i.e., soil water table) affect the carbon respirations. A study had been conducted to ascertain the effects of water table levels on soil CO2 respirations of West Kalimantan coastal forested and bare peatland. We simulated natural intact peat core condition by designing 25 of "a double bucket" water level experiment using 5 levels of water tables (0-40cm) and measure soil CO2 respiration at soil surfaces. Results showed that water table levels significantly affected soil CO2 respiration, as well as peat microclimate conditions. Results also demonstrated that forest canopy had significant effects on reducing peat CO2 respiration through its function in maintaining site-environment conditions compared to bare peatland site. This study reveals that it is important to maintain peatland water level close to peat surface and to maintain forest/vegetation covered on peatlands to reduce soil CO2 emissions.